Carta de Rafael Martínez Nadal a Roberto H. Todd - Martínez Nadal, Rafael; Todd, Roberto H. (My University, 1926)
Reunión de los presidentes de los partidos con el Gobernador.
Keywords: Republican party. Puerto Rico.; Tous Soto, José, 1874-1933; Barceló, Antonio R., 1868-1938; Partido Republicano (Puerto Rico)